Copper-catalyzed N-(hetero)arylation of amino acids in water. Issue 99 (11th October 2016) - Sharma, Krishna K.; Mandloi, Meenakshi; Rai, Neha; Jain, Rahul
Abstract : A transition metal-catalyzed, environmentally benign, rapid and cost-effective method for the N -(hetero)arylation of zwitterionic amino acids in water is reported. Abstract : An environmentally benign, mild, cost-effective and gram-scalable copper-catalyzed method for the N -(hetero)arylation of zwitterionic natural and unnatural amino acids using 2-isobutyrylcyclohexanone as a β-diketone ligand and aryl bromides as coupling partners in water for 50 min at 90 °C under microwave irradiation is reported. Electronically and sterically diverse aryl coupling partners were inserted efficiently, including challenging heteroaryl electrophilic partners in high yields without affecting the enantiopurity of the product.